2000
DOI: 10.1084/jem.192.7.1059
|View full text |Cite
|
Sign up to set email alerts
|

Dap10 and Dap12 Form Distinct, but Functionally Cooperative, Receptor Complexes in Natural Killer Cells

Abstract: Many of the activating receptors on natural killer (NK) cells are multisubunit complexes composed of ligand-binding receptors that are noncovalently associated with membrane-bound signaling adaptor proteins, including CD3ζ, FcεRIγ, DAP12, and DAP10. Because the DAP10 and DAP12 genes are closely linked, expressed in NK cells, and have remarkably similar transmembrane segments, it was of interest to determine the specificity of their interactions with ligand-binding receptors and to examine their signaling prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
161
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(176 citation statements)
references
References 34 publications
(49 reference statements)
9
161
2
Order By: Relevance
“…Previous studies demonstrated the requirement for Vav proteins in NK cytotoxicity mediated by ITAM-containing adaptors such as DAP12 and FcR␥; however, evidence for the requirement for Vav proteins downstream of the DAP10-associated receptor NKG2D has been complicated by the fact that murine NKG2D associates with both DAP10 and DAP12 (13)(14)(15). In this report, we provide genetic evidence for the critical role of Vav1 in natural cytotoxicity induced by NKG2D-DAP10 in the absence of DAP12-generated ITAM signals.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous studies demonstrated the requirement for Vav proteins in NK cytotoxicity mediated by ITAM-containing adaptors such as DAP12 and FcR␥; however, evidence for the requirement for Vav proteins downstream of the DAP10-associated receptor NKG2D has been complicated by the fact that murine NKG2D associates with both DAP10 and DAP12 (13)(14)(15). In this report, we provide genetic evidence for the critical role of Vav1 in natural cytotoxicity induced by NKG2D-DAP10 in the absence of DAP12-generated ITAM signals.…”
Section: Discussionmentioning
confidence: 57%
“…Subsequent to ligand engagement, human NKG2D signals through DAP10, whereas murine NKG2D signals through distinct adaptor molecules. Full-length NKG2D-long (NKG2D-L) signals through DAP10, whereas a shorter splice variant (NKG2D-S) signals through both DAP10 and DAP12 (13)(14)(15). In this regard, the relative proportion of NKG2D-L and NKG2D-S in NK cells varies upon in vitro activation with IL-2.…”
mentioning
confidence: 99%
“…The NKG2D/DAP12 complexes are undetectable in human NK cells. On the contrary, NKG2D in the murine NK cells associates with either DAP10 or DAP12, whereas the expression of NKG2D/DAP12 complexes become predominant following cytokine activation (45). Interestingly, in this study, anti-NKG2D-mediated activation specifically resulted in the phosphorylation of PLC␥2, and the phosphorylation of PLC␥1 was undetectable, which could be due to high and low expression levels of PLC␥2 and PLC␥1, respectively, in murine NK cells.…”
Section: Discussionmentioning
confidence: 63%
“…This interpretation cannot apply to the monoclonal anti-NKp46, which is an IgM and therefore unable to mediate redirected lysis. In contrast, the monoclonal anti-NKG2D is an IgG1 known to redirect NK cell lysis toward the P815 mastocytoma cell line (63). Consequently, we compared the viability of infected DCs when cultured with NK cells in the presence or absence of anti-NKG2D (Fig.…”
Section: Nkg2d Nkp46 and Il-12 Contribute To Enhanced Ifn-␥ Productmentioning
confidence: 99%